Constraining the Moho Depth Below Bhutan With Global-Phase Seismic Interferometry - Obermann, Anne; Ruigrok, Elmer; Bianchi, Irene; Hetényi, György (Frontiers in Earth Science, 2021)
We use a novel technique named Global-Phase Seismic Interferometry (GloPSI) to image the lithospheric structure, and in particular the Moho, below two parallel north-south transects belonging to the GANSSER network (2013-2014). The profiles cross the Himalayan orogenic wedge in Bhutan, a tectonically important area within the largest continent-continent collision zone on Earth that is still undergoing crustal thickening and represents a challenging imaging target for the GloPSI approach. GloPSI makes use of direct waves from distant earthquakes and receiver-side reverberations with near vertical incidence. Reflections are isolated from earthquake recordings by solving a correlation integral and are turned into a reflectivity image of the lithosphere below the arrays. Our results compare favourably with first-order features observed from a previous receiver function (RF) study. We show that a combined interpretation of GloPSI and RF results allows for a more in-depth understanding of the lithospheric structure across the orogenic wedge in Bhutan.